Combining In Vivo and Organotypic In Vitro Approaches to Assess the Human Relevance of Basimglurant (RG7090), a Potential CAR Activator. (27th May 2020) - Nudischer, Ramona; Renggli, Kasper; Bertinetti-Lapatki, Cristina; Hoflack, Jean-Christophe; Flint, Nicholas; Sewing, Sabine; Pedersen, Lykke; Schadt, Simone; Higgins, Larry G; Vardy, Audrey; Lenz, Barbara; Gand, Laurent; et al.
Abstract: Basimglurant (RG7090), a small molecule under development to treat certain forms of depression, demonstrated foci of altered hepatocytes in a long-term rodent-toxicity study. Additional evidence pointed toward the activation of the constitutive androstane receptor (CAR), an established promoter of nongenotoxic and rodent-specific hepatic tumors. This mode of action and the potential human relevance was explored in vivo using rodent and cynomolgus monkey models and in vitro using murine and human liver spheroids. Wild type (WT) and CAR/pregnane X receptor (PXR) knockout mice (CAR/PXR KO) were exposed to RG7090 for 8 consecutive days. Analysis of liver lysates revealed induction of Cyp2b mRNA and enzyme activity, a known activation marker of CAR, in WT but not in CAR/PXR KO animals. A series of proliferative genes were upregulated in WT mice only, and immunohistochemistry data showed increased cell proliferation exclusively in WT mice. In addition, primary mouse liver spheroids were challenged with RG7090 in the presence or absence of modified antisense oligonucleotides inhibiting CAR and/or PXR mRNA, showing a concentration-dependent Cyp2b mRNA induction only if CAR was not repressed. On the contrary, neither human liver spheroids nor cynomolgus monkeys exposed to RG7090 triggered CYP2B mRNA upregulation. Our data suggested RG7090 to be a rodent-specific CAR activator, and that CAR activation and its downstream processes were involved in the foci of altered hepatocytes formation detected in vivo . Furthermore, we demonstrated the potential of a new in vitro approach using liver spheroids and antisense oligonucleotides for CAR knockdown experiments, which could eventually replace in vivo investigations using CAR/PXR KO mice.